Diversity and distribution of the marine and estuarine shrimps (Dendrobranchiata, Stenopodidea and Caridea) from North and Northeast Brazil - Coelho, Petrônio Alves; de Almeida, Alexandre Oliveira; de Souza-Filho, Jesser Fidelis; Bezerra, Luis Ernesto Arruda; Giraldes, Bruno Welter (Zootaxa, 2006)
The present study aimed to evaluate the current state of knowledge of marine and estuarine shrimp species from the suborder Dendrobranchiata and the infraorders Stenopodidea and Caridea, considering their diversity and distribution along the North and Northeast Brazilian coast (N/NE). The number of reported species rose from 124 to 169 since the Paulo S. Young’s Catalogue of Crustacea of Brazil, put out in 1998, which means an increase of 36.3%.  Pernambuco (89 species) and Bahia (68 species) are the states that present the highest shrimp diversity, accounting for 53% and 40.5% of the total species registered for the N/NE regions, respectively. On the other hand, the states of Sergipe (21 species) and Piauí (13 species) contributed with only 12.5% and 7.7% of the total species registered at the moment.